Coexisting morphea with lichen sclerosus et atrophicus in a single lesion - a rare case report - Das, Abhijit; Gupta, Srishti; Singh, Sompal; Pant, Leela (Bangladesh Journal of Medical Science, 2016)
Background: Lichen sclerosus et atrophicus (LSA) is an inflammatory dermatitis of unknown etiology affecting usually genital region with rare involvement of extragenital regions like face, neck, shoulder etc. Coexistence of lichen sclerosus et atrophicus and morphea is a very rare finding. Although LSA at early stage and morphea can be differentiated clinically and histologically, both diseases at late stage present diagnostic difficulties. Case presentation: We reported a 4-year-old female child presented with a non-pruritic hypopigmented sclerotic patch over left shoulder. Histopathology showed features consistent with both LSA and morphea in the same lesion. Conclusion: Coexistence of both LSA and morphea in same patient suggests that these lesions represent a spectrum of diseases which may reflect similar events or closely related pathologic process. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.145-147